1986
DOI: 10.1177/00220345860650021001
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Demineralization and the Length of Intra-oral Exposure to Different Concentrations of Glucose or Sucrose

Abstract: Six subjects wore intra-oral devices carrying eight bovine enamel blocks which were covered with a layer of S. mutans. They rinsed their mouths for five sec, one min, or multiples of one min with a 5 or 10% glucose (G) solution. Demineralization was measured after 45 min by determining the change in iodide permeability (delta Ip) of the enamel. In addition, saliva samples, taken at intervals during the test, were analyzed for G, and the time of clearance (tc) was calculated. Demineralization scores (delta Ip) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
6
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
3
6
0
Order By: Relevance
“…This was also found to be the case in a previous study of glucose rinses in which the same experimental period of 45 min was used [Tehrani et al, 1986]. The pH of the S. mutans cells employed in our system follows a Stephan curve [Brudevold et al, 1984a, b] and was on the rise at the time it was mea sured, 42 min following the last substrate exposure.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This was also found to be the case in a previous study of glucose rinses in which the same experimental period of 45 min was used [Tehrani et al, 1986]. The pH of the S. mutans cells employed in our system follows a Stephan curve [Brudevold et al, 1984a, b] and was on the rise at the time it was mea sured, 42 min following the last substrate exposure.…”
Section: Discussionsupporting
confidence: 62%
“…The correlation coefficient was much higher for the maltose in the spittings than for the tc (0.60 vs. 0.44). Previous studies on mouthrinses with solutions of glucose or suspen sions of 10% starch have also shown a closer correla tion with the high concentrations initially present in the mouth than with the decreasing concentrations during the process of clearance [Tehrani et al, 1986;Brudevold et al, 1985]. A reasonable explanation would be that substrate diffuses rapidly into the plaque in the presence of high oral concentrations and that the rate of diffusion decreases and eventually is reversed as salivary concentrations are reduced.…”
Section: Discussionmentioning
confidence: 83%
“…It also appears important to reconsider the com mon recommendation that teeth should be cleaned 'after meals' because our results indicated that the ca ries inhibition by mechanical cleaning was related more to the suppression of established plaque metab olism rather than to the removal of food remnants. The need for a reconsideration of the classical aftermeal-brushing-instruction, as also suggested by Black [1908] and advocated by Jenkins [1960], is supported by recent observations indicating that significant de mineralization may occur while carbohydrate foods are consumed [Tehrani et al, 1986].…”
Section: Discussionmentioning
confidence: 92%
“…In humans, studies have been limited, of ne cessity, to the demonstration of influences on plaque pH [Edgar, 1985;Jensen and Schachtele, 1983], or on hardness of enamel blocks treated repeatedly in vitro and worn in the mouth [Essig et al, 1985;Silva et al, 1986]. Earlier studies in this laboratory have led to the development of an intraoral test system that measures progressive demineralization of enamel blocks in 1 This investigation was supported by Research Grant DE-05253 from the National Institute of Dental Research, US Public Health Service vivo by following changes in the permeability of the blocks to iodide [Brudevold et al" 1984], Ingestion of solutions of various dietary sugars was shown to bring about loss of mineral and the extent of deminer alization reflected the concentration of sugar, or the frequency of its use [Tehrani et al, 1983[Tehrani et al, , 1986, Following the successful use of the iodide permea bility (delta Ip) system with sugar solutions, it was im portant to determine whether it could be used with solid foods in a sensitive and reproducible manner. If applicable, the intraoral test system would make pos sible the evaluation of the cariogenic potential of dif ferent foods under highly standardized conditions.…”
mentioning
confidence: 99%